Pengaruh Perlakuan Benih Dan Jenis Mulsa Terhadap Penyakit Antraknosa Tanaman Cabai Rawit (Capsicum Frutescens L.) Di Desa Walitelon Selatan Kecamatan Temanggung - Ramadhanti (Indoensia), Safira Putri; rahmiyah (Indoensia), Muzayyanah; Laeshita (Indoensia), putri (JURNAL VIGOR, 2024)
Anthracnose is a disease that often found in chilli plants caused by Colletotrichum sp. This research aims to examine seed treatment and mulch type on their ability to suppress anthracnose disease in chilli plants (Capsicum frutescens L.). The research was conducted in Walitelon Selatan Village, Temanggung District, Temanggung Regency at an altitude of 550 meters above sea level with alfisol soil type. This research was structured using a complete randomized block design with two treatment factors and 3 replications as blocks. The first factor, seed treatment, soaking with plain water (P1) and soaking with T. harzianum L. (P2). The second factor is the treatment of different types of mulch (M1) without mulch, (M2) rice straw mulch, (M3) silver-black plastik mulch, (M4) bamboo leaf litter mulch. The results showed that soaking seeds using T. harzianum L. (P2) had a significant effect in reducing the incidence of anthracnose disease and the percentage of diseased fruits. The use of black silver plastic mulch (M3) has a significant effect on plant height, healthy fruit weight, incidence of anthracnose disease, percentage of diseased fruit, and percentage of healthy fruit. The interaction of seed soaking using water and black silver black plastic mulch (P1M3) has a significant effect on fruit weight and percentage of healthy fruit. The conclusion is T. harzianum L. and black silver plastic mulch can reduce anthracnose disease.